Advances in Barrier Membranes for Guided Bone Regeneration Techniques - Yang, Ze; Wu, Chang; Shi, Huixin; Luo, Xinyu; Sun, Hui; Wang, Qiang; Zhang, Dan (Frontiers in Bioengineering and Biotechnology, 2022)
Guided bone regeneration（GBR）is a widely used technique for alveolar bone augmentation. Among all the principal elements, barrier membrane is recognized as the key to the success of GBR. Ideal barrier membrane should have satisfactory biological and mechanical properties. According to their composition, barrier membranes can be divided into polymer membranes and non-polymer membranes. Polymer barrier membranes have become a research hotspot not only because they can control the physical and chemical characteristics of the membranes by regulating the synthesis conditions but also because their prices are relatively low. Still now the bone augment effect of barrier membrane used in clinical practice is more dependent on the body's own growth potential and the osteogenic effect is difficult to predict. Therefore, scholars have carried out many researches to explore new barrier membranes in order to improve the success rate of bone enhancement. The aim of this study is to collect and compare recent studies on optimizing barrier membranes. The characteristics and research progress of different types of barrier membranes were also discussed in detail.